Importanța mecanismelor ONU în promovarea și respectarea drepturilor omului în regiunea transnistreană a Republicii Moldova [Articol] - Cazacu, Pavel (CEP USM, 2021)
Because the Transnistrian region is not temporarily controlled by the constitutional authorities of the Republic of Moldova, the promotion and protection of human rights in this region remains an ongoing challenge. Thus, international mechanisms for the protection of human rights are important. The mechanisms of the UN, together with those within the Council of Europe, are the most relevant and effective mechanisms for the protection of human rights, including for territories not temporarily controlled by the constitutional authorities.
THE IMPORTANCE OF UN MECHANISM IN PROMOTING AND RESPECTING HUMAN RIGHTS IN THE TRANSNISTRIAN REGION OF THE REPUBLIC OF MOLDOVA
Keywords: human rights; the Transnistrian region; international human rights mechanisms; UPR